An integrated AHP–composite priority index model for determining tourism village development priorities: evidence from Jember Regency, Indonesia - Faozen Faozen; Cristian Rizqi Anggraini (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2026)
The development of tourism villages has become an important strategy to stimulate rural economic growth through community-based tourism. However, the determination of priority tourism villages is frequently conducted without a systematic and transparent decision-making framework, which may result in inefficient allocation of development resources. This study aims to develop a priority model for tourism village development by integrating internal and external factors using the Analytic Hierarchy Process (AHP) and a Composite Priority Index (CPI). A quantitative multi-criteria decision-making approach was applied, involving seven experts representing government institutions, academic researchers, and tourism village practitioners. Pairwise comparisons were conducted using Saaty’s scale to determine the relative weights of development criteria, while the CPI was used to calculate the final priority ranking of tourism villages. The results reveal that within the internal dimension, institutional capacity and governance (0.28) represent the most influential factor, followed by human resources and tourism awareness groups (0.23), attractions (0.19), amenities (0.17), and environmental sustainability (0.13). Within the external dimension, strategic partnerships (0.27) emerge as the dominant factor, followed by budget support (0.23), government policy support (0.21), accessibility (0.17), and promotion (0.12). Based on the composite index calculation, tourism villages are categorized into high, medium, and low priority clusters, providing a structured framework for phased development interventions. These findings highlight that tourism village sustainability depends not only on tourism potential but also on strong institutional governance and collaborative networks. The proposed model offers an evidence-based decision support system to assist local governments in determining tourism village development priorities more objectively and strategically.